An EMMS drag model for coarse grid simulation of polydisperse gas–solid flow in circulating fluidized bed risers. (2nd November 2019) - Qin, Zhiyuan; Zhou, Quan; Wang, Junwu
Highlights: An EMMS drag model was established for polydisperse flow. Coupled EMMS drag model and multifluid model was used for CFD simulations. The EMMS drag model predicted a better hydrodynamics and axial particle size distribution compared to Gidaspow drag model. Both gas-particle and particle-particle drag models are important. Particle phase stress has a minor effect on CFD results. Abstract: Polydisperse gas–solid systems are more common in both industry and the natural world than their monodisperse counterparts. This paper aims to investigate the hydrodynamics of polydisperse gas–solid flow systems by extending the energy minimization multiscale (EMMS) drag model. The continuous particle size is discretized into several characteristic sizes, by which the polydisperse particles are classified into several discrete groups. A polydisperse EMMS drag model is then developed by treating these particle groups as solid phases. Finally, the proposed drag model is coupled with the multifluid model to simulate the hydrodynamics of polydisperse gas–solid flow in CFB risers. Extensive simulations are conducted to validate the effectiveness of the polydisperse EMMS drag model and investigate the effects of gas–particle drag models, kinetic theories, and particle–particle drag models on the simulation results. It was found that (i) the polydisperse EMMS drag model can predict the concentration and particle size distribution of polydisperse gas–solid flows better than the traditional drag model; (ii) the particle–particle drag force has an important influence on the mixing and segregation of different particles whereas the particulate phase stress has only a very minor effect, especially when the superficial gas velocity is low. The second finding highlights the need for a suitable particle–particle drag model that considers the effects of mesoscale structures, which will be the topic of our future study.